Pengaruh Ketersediaan Sarana Prasarana Teknologi Sekolah terhadap Motivasi Belajar Siswa Kelas X Jurusan TJKT di SMK Negeri 1 Sukoharjo - Pawitra, Puruhita Mega; Budiyanto, Cucuk Wawan; Raharjo, Joko Slamet (Indonesian Journal of Learning and Instructional Innovation, 2024)
This study examines the influence of the availability of technology facilities and infrastructure on the learning motivation of 10th-grade TJKT students at SMK N 1 Sukoharjo. Using a mixed- methods approach, quantitative data were collected through questionnaires distributed to 60 students, while qualitative data were gathered through observations during PPL activities. The results indicate that the availability of adequate computer devices, software, and laboratories significantly supports the learning process and enhances students' creativity and motivation. Observations revealed that students were more enthusiastic and actively engaged in learning with the use of technology. However, some challenges were identified, such as insufficient number of devices and the need for improved internet stability. These findings suggest that increasing the quantity and quality of technological devices and improving internet stability are crucial for creating a more conducive learning environment, thereby enhancing students' motivation and learning outcomes. Practical recommendations include that policymakers in the education sector should continue to invest in up-to-date technological facilities and infrastructure and ensure equal access for all students.